Commerce, services and city structuring: socio-spatial inequality in consumption in Londrina, Paraná, Brazil (PerCursos, 2023)
Throughout the urbanization process, economic activities linked to the spheres of commerce, services and consumption have always played fundamental roles in urban life, composing the structuring of cities in their forms, processes and contents. This article aims to analyze the city of Londrina, in the state of Paraná, Brazil, in its current phase of socio-spatial structuring, encompassing the distribution pattern of commercial and service establishments, ongoing spatial processes and spatial practices oriented by consumptive consumption. To achieve this, we adopted various methodological procedures, both quantitative and qualitative: we combined data from the National Register of Addresses for Statistical Purposes (CNEFE) and information from the National Classification of Economic Activities (CNAE) to assess the special distribution pattern of establishments, which appeared to be multicentric and multicentralized. To understand the empirical aspect of this distribution, we conducted fieldwork in localities within the research area. In order to grasp the contents related to spatial practices, interviews were conducted with city residents and shopkeepers. Gathering the results obtained, we characterize that the current phase of spatial structuring of Londrina reveals socio-spatial inequality, stemming from the spheres of commerce and consumption.
Keywords: consumptive consumption; spatial practices; multicentrality; geographic scales; urban agglomeration of Londrina